Kajian Pertumbuhan dan Produksi Kentang (Solanum tuberosum L.) dengan Variasi Umbi Benih: Study Growth and Production of Potatoes (Solanum Tuberosum L.) with Variations in Seed Tubers - Suryaningsih, Dwi Retna; Haryanta, Dwi (Agrocentrum, 2024)
The effect of seed tuber weight on the growth and production of potatoes (Solanum tuberosum L.) is intended to determine the efficiency of using tubers as seed material in potato cultivation. The single factor experiment was carried out using a randomized block design (RAK) consisting of 8 treatments, namely treatment A (Granolla variety with tuber weight 28 – 30 g), B (Granolla variety with tuber weight 31 – 45 g), C (Granolla variety with tuber weight 46 – 60 g), D HPS variety with tuber weight 31 – 45 g (Granolla variety with tuber weight 61 – 80 g), E (HPS variety with tuber weight 28 – 30 g), F (HPS variety with tuber weight 31 – 45 g), G (HPS variety with tuber weight 46 – 60 g), and H treatment (HPS variety with tuber weight 61 – 80 g). Each treatment was repeated four times. The results showed that the results were better for tubers weighing 46 - 60 g than tubers weighing 28 - 45 g, and the results were the same compared to tubers weighing 61 - 80 g, both for the HPS variety and the granolla variety. In developing potato cultivation, it is necessary to pay attention to the availability of quality seeds, the weight of the seed tubers and varieties that are suitable for the land environment. By increasing the production of quality tuber seeds, it is hoped that it can contribute to increasing productivity and potato production